Manejo y evolución de fibrilación auricular en el postoperatorio de cirugía cardiaca - Cereceda B., Mauricio; Solanes , Federica; Zamorano G. , Jaime (Revista Hospital Clínico Universidad de Chile, 2008)
Introduction: postoperative atrial fibrillation (POAF) is the most frequent arrhythmia in patients that undergo a cardiac surgery. POAF’s prevalence ranges from 10 to 65%. Most initial episodes of POAF occurred within the first few days alter cardiac surgery. The prevention of POAF is well known but there are no guidelines and no randomized clinical trial that have evaluated the acute management of the arrhythmia. The aim of this restrospective study was to know the management and intrahospital evolution of patients with POAF in our institution. Main results: among 426 patients undergoing a cardiac surgery, the incidence of POAF was 10%. We analyzed only 27 patients of the 42 with POAF. Five patients spontaneously restored sinus rhythm (SR) and in the others, the first approach to the management was with betablockers in 15 patients (70%). To restore SR, the treatment of choice was pharmacological, only with amiodarone, with 70% of conversion to SR. Only three patients needed direct current cardioversion to restore SR. At discharge 5 patients were in AF. Conclusion: the management and evolution of patients with POAF in our institution is similar than reported experiences. The initial treatment is to achieve rate control mainly with betablockers. To restore SR the drug of choice is amiodarone with an efficacy of 70%. In the minority of our patients direct current cardioversion was necessary to recover SR. Nearly 19% of POAF patients were discharged on AF and 44% with antiarrhythmic drugs.